Features of Feingold syndrome 1 dominate in subjects with 2p deletions including MYCN. Issue 9 (8th August 2018) - Burnside, Rachel D.; Molinari, Sharon; Botti, Christina; Brooks, Susan Sklower; Chung, Wendy K.; Mehta, Lakshmi; Schwartz, Stuart; Papenhausen, Peter
Abstract : Interstitial deletions of the distal short arm of chromosome 2 including MYCN have only been reported for a small number of individuals. Germline deletions and mutations of MYCN cause Feingold syndrome 1 (FS1), a rare disorder characterized by microcephaly, digit anomalies, gastrointestinal atresias, short stature, dysmorphic features, and intellectual disability. We present a series of six individuals referred for SNP microarray with overlapping deletions of 2p ranging from 3.4 to 16.8 Mb in size, with a common overlapping region of 1.53 Mb spanning (14, 614, 477–16, 148, 021) [hg19] and including five genes: NBAS, DDX1, MYCNUT, MYCNOS, and MYCN . Clinical information was available for five individuals. Clinical features included core features of FS1 such as microcephaly, digit anomalies, and gastrointestinal atresias as well as structural cardiac defects, hearing loss, and renal anomalies, which are features less consistently associated with FS1. Other features observed in several individuals, that have not specifically been associated with FS1 were motor delay, structural brain abnormalities, genital abnormalities, and radioulnar synostosis. These results indicate that while individuals with deletions of 2p spanning several megabases and including MYCN can present with features not typically associated with FS1, the common core features are usually present.